San Pedro Atlapulco y la Real Casa de Moneda: las vicisitudes de una empresa comunitaria - Castro Gutiérrez, Felipe (El Colegio de México, A.C., 2008)
This work suggests the existence of very interesting exceptions to the widespread idea that New Spain indians were farmers who produced basically for their own needs and for paying tribute, thus limiting their contacts with the market. The author  examines the case of Atlapulco, a town that very soon became the main provider of charcoal as fuel for the official mint, the Real Casa de Moneda in Mexico City. The research reveals Atlapulco’s constant  battle against the arrival of indian and Spanish competitors seeking a share in the deal, suggesting that the main reason for this attitude was the preservation of a lucrative monopoly, considered a special privilege granted by the king. The author also describes the disputes between Atlapulco  and the mint administrators over fixing con tractually the price of charcoal. Finally, he examines the discourse used by Indians in the defense of their interests, pointing out how they appealed to the idea that commercial arrangements must necessarilly take into account tradition, historical rights and mutual obligations sustaining social order.